Soils in the Slovenian educational system - Repe, Blaž (Bulletin of Geography. Physical Geography Series, 2018)
There is a considerable amount of confusion in the topics regarding soils on all levels of Slovenian education. The fundamental problem is the naming for soil itself. Several different names appear for soil that deal with more or less the same natural phenomenon. Other problems include lack of official Slovenian soil classification, sometimes out of date soil topics in primary and secondary school, inexpert use of soil names for soil types of the World, none existing special soil studies. There are a lot of existing initiatives to improve the current state, but the differences among soil scientists are impeding the process.